Strategies Used by EFL Students to Overcome Challenges in the Structure & Written Expression Section of the TOEFL - Mutmainnatussafiyyah, Mutmainnatussafiyyah; Sakkir, Geminastiti; Sally, Fauzan Hari Sudding (Journal of Excellence in English Language Education, 2025)
This study explores the strategies used by EFL students to overcome challenges in the Structure and Written Expression section of the TOEFL ITP test. This study employs a qualitative descriptive method. The data were gathered through semi-structured interviews with five English Department students at Universitas Negeri Makassar who had previously taken the TOEFL ITP. The findings reveal that students adopted a range of self-developed strategies to address common difficulties, such as regular practice, active vocabulary-building, understanding TOEFL question formats, strengthening grammar skills, improving time management, boosting self-confidence, and setting clear goals. These findings are further reinforced by relevant literature. In conclusion, EFL students at Universitas Negeri Makassar actively develop effective strategies to mitigate the challenges and enhance their test performance.